TELENURSING-BASED HEALTH EDUCATION VIA WHATSAPP GROUP FOR ELDERLY WITH HYPERTENSION - I Gede Restawan; Ni Luh Emilia; Yulisti Ewagola; A'an Greysia Mewalo; Angrifa Yuliani Tangkeda; Zahrotusholihah (Universitas Islam Negeri Alauddin Makassar, 2025)
One of the most prevalent chronic conditions among the elderly is hypertension, which raises the risk of cardiovascular problems. Using communication tools like WhatsApp groups, telenursing can enhance blood pressure control and health literacy. This study shows how older people with hypertension and knowledge are affected by health education through telenursing via WhatsApp groups. A pretest-posttest control group was included in the quasi-experimental study design. Elderly individuals with hypertension who were split into intervention and control groups made up the sample. The intervention group received health education via WhatsApp, whereas the control group received normal education at a health institution. Parametric statistical tests were used to assess knowledge, systolic, and diastolic blood pressure data at a significance level of p<0.05. The findings demonstrated that the intervention group's knowledge had significantly increased (from 6.39±1.32 to 12.14±1.35, p<0.001) in contrast to the control group (from 6.57±1.43 to 9.18±2.02, p<0.001). The intervention group experienced a significant decrease in systolic blood pressure (154.36±9.07 to 127.86±10.69 mmHg, p<0.001) compared to the control group (158.57±18.36 to 144.89±18.67 mmHg, p<0.001). The decrease in diastolic blood pressure was significant in both groups, but not significant between groups (p=0.387). Conclusion: WhatsApp group-based telenursing improves knowledge and reduces systolic blood pressure in elderly with hypertension. This technique is recommended for further research and community support with longer intervention durations, as well as for cost-effectiveness analyses.